HELEN’S CHARACTER: A CRITICAL ANALYSIS - Choudhurimayum Silpa (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In Greek Mythology, Helen was the daughter of Zeus and Leda, and was considered the most beautiful woman in the world of the time. She was married to Menelaus, the king of Sparta, but fled to Troy with Paris, the son of the Trojan king Priam. This act caused the Trojan War, which lasted for ten years. After the war, Helen returned to Sparta with Menelaus. In order to know the character of Helen clearly, it is analysed at five levels as shown in this article. The five levels are : a) Helen as a daughter, b) Helen as a wife, c) Helen as a daughter-in-law, e) Helen as a mother, and f) Helen as a woman.